2015
DOI: 10.1017/neu.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Serum total oxidant and antioxidant status in earthquake survivors with post-traumatic stress disorder

Abstract: Our results suggest that the total oxidant and antioxidant status may not affect earthquake survivors with PTSD. This is the first study to evaluate the oxidative status in earthquake survivors with PTSD. Further studies are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…As part of a magnetic resonance spectroscopy (MRS) study, Michaels et al (48) examined the dorsolateral prefrontal cortex and anterior cingulate cortex among 29 trauma-exposed individuals (12 with PTSD and 17 without PTSD), and found those with PTSD had significantly higher levels of the antioxidant, glutathione in both regions, which may represent a compensatory reaction to increased oxidation (it may also represent an excess of antioxidant activity for unclear reasons). Ozdemir et al (49) recently reported a lack of significant group differences in total antioxidant or oxidative status among Turkish earthquake survivors with and without PTSD, and also did not find significant correlations between severity of PTSD symptoms and oxidative measures. Overall, the results from studies of PTSD and oxidative markers appear mixed at best, but given the limited availability of studies with overlapping methods or outcomes measures, and the small samples sizes within several of the available studies, it seems premature to draw firm conclusions regarding the presence or absence of an association of PTSD with oxidative stress.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As part of a magnetic resonance spectroscopy (MRS) study, Michaels et al (48) examined the dorsolateral prefrontal cortex and anterior cingulate cortex among 29 trauma-exposed individuals (12 with PTSD and 17 without PTSD), and found those with PTSD had significantly higher levels of the antioxidant, glutathione in both regions, which may represent a compensatory reaction to increased oxidation (it may also represent an excess of antioxidant activity for unclear reasons). Ozdemir et al (49) recently reported a lack of significant group differences in total antioxidant or oxidative status among Turkish earthquake survivors with and without PTSD, and also did not find significant correlations between severity of PTSD symptoms and oxidative measures. Overall, the results from studies of PTSD and oxidative markers appear mixed at best, but given the limited availability of studies with overlapping methods or outcomes measures, and the small samples sizes within several of the available studies, it seems premature to draw firm conclusions regarding the presence or absence of an association of PTSD with oxidative stress.…”
Section: Resultsmentioning
confidence: 96%
“…We found five studies relevant to PTSD and oxidative measures (18, 46–49). Tezcan et al (18) compared 14 people with PTSD and 14 hospital staff used as comparison subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Özdemir et al [ref#? ] did not find a significant difference in total oxidant and antioxidant parameters in their study with adults with post-traumatic stress disorder; however, a significant difference in lipid peroxidation markers and prolidase among sub-parameters was found in other studies [43][44][45]. These data led us to understand the functional neurological disorder better, and assessing oxidative stress sub-parameters might be more useful before the deterioration of oxidative capacity affects total antioxidant capacity.…”
Section: Discussionmentioning
confidence: 82%
“…Of course, there are still a lot of controversies regarding the relevance of the oxidative stress status in most of the affective disorders and despite the fact that most of the studies are showing that the affective disorders development can be correlated to increased oxidative levels (as we showed for most of the shortly described studies above), there are also some distinct studies reporting that oxidative stress may not be linked in any way, for example, with PTSD [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 91%